AFK-PD alleviated osteoarthritis progression by chondroprotective and anti-inflammatory activity - Qian, Zhuang; Xu, Jie; Zhang, Lei; Deng, Qian; Fan, Zhenlin; Guo, Xueqiang; Liang, Zhuo; Wang, Weiyun; Wang, Lei; Liao, Xiaohua; Ren, Wenjie (Frontiers in Pharmacology, 2024)
Osteoarthritis (OA) is the most prevalent cartilage degenerative and low-grade inflammatory disease of the whole joint. However, there are currently no FDA-approved drugs or global regulatory agency-approved treatments OA disease modification. Therefore, it's essential to explore novel effective therapeutic strategies for OA. In our study, we investigated the effects of AFK-PD, a novel pyridone agent, on the development of OA induced by destabilization of the medial meniscus (DMM) in vivo, and its impact on the function of chondrocytes treated with IL-1β in vitro. Our results demonstrated AFK-PD alleviated OA progression through inhibiting cartilage degeneration, articular inflammation and osteophyte formation. Notably, AFK-PD inhibited chondrocyte inflammation and synovial macrophage M1 polarization, leading to the attenuation of articular inflammation. Additionally, AFK-PD promoted chondrocyte anabolism while mitigating catabolism and apoptosis, effectively inhibiting cartilage degeneration. Mechanistically, AFK-PD suppressed the expression of key signaling molecules involved in the MAPK pathway, such as p-ERK1/2 and p-JNK, as well as the NF-κB signaling molecule p-p65, in IL-1β-induced chondrocytes. These findings suggest AFK-PD ameliorates the development of OA by protecting chondrocyte functions and inhibiting articular inflammation in chondrocytes and synovial macrophages. Overall, our study highlights AFK-PD as a promising therapeutic candidate for the treatment of OA.